Association study of genetic variants in eight genes/loci with type 2 diabetes in a Han Chinese population - Ma Shi; Chen Ming; Rao Shaoqin; Liu Xiaoqi; Lu Fang; Wang Li; Yang Yang; Xian Yang; Li Ying; Zhang Xuejun; Tang Xin; Zhang Ben; et al. (BMC, 2010)
Abstract Background At least twenty genes/loci were shown to be associated with type 2diabetes in European original populations. Five of these genes were shown to be associated with type 2 diabetes (T2D) in Chinese populations. The purpose of this study was to replicate the association of genetic vairants in the eight diabetes-related genes/loci with type 2 diabetes in a Han Chinese cohort from western part of China. Nineteen single nucleotide polymorphisms (SNPs) from the eight genes/loci including TCF7L2, HHEX, CDKAL1, SLC30A8, PPARG, IGF2BP2, KCNJ11, and CDKN2A/CDKN2B were genotyped in 1,529 cases and 1,439 controls in a Han Chinese population using the ABI SNaPshot method. The meta-analysis of the association between rs7903146 in TCF7L2 gene and T2D in the Han Chinese was performed. Results Among the eight genes/loci examined, we found that four were significantly associated with T2D. Although previous studies showed that the association between the SNP rs7903146 in the TCF7L2 gene and T2D was controversial within the Han Chinese population, we have confirmed the significant association between the SNP rs7903146 in the TCF7L2 gene and T2D in both this study and the meta-analysis in the population. In addition, we also confirmed that three SNPs (rs1111875, rs7923837 and rs5015480) in HHEX , one SNP (rs10946398) in CDKAL1, and three SNPs (rs13266634, rs3802177 and rs11558471) in SLC30A8 were significantly associated with T2D in the population being studied. Conclusions We demonstrated that the variants in TCF7L2, CDKAL1, HHEX, and SLC30A8 genes are associated with T2D in a Han Chinese population.